2010
DOI: 10.1073/pnas.0903269107
|View full text |Cite
|
Sign up to set email alerts
|

Geometric cues for directing the differentiation of mesenchymal stem cells

Abstract: Significant efforts have been directed to understanding the factors that influence the lineage commitment of stem cells. This paper demonstrates that cell shape, independent of soluble factors, has a strong influence on the differentiation of human mesenchymal stem cells (MSCs) from bone marrow. When exposed to competing soluble differentiation signals, cells cultured in rectangles with increasing aspect ratio and in shapes with pentagonal symmetry but with different subcellular curvature-and with each occupyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

91
1,559
5
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 1,633 publications
(1,680 citation statements)
references
References 51 publications
91
1,559
5
3
Order By: Relevance
“…We demonstrated that the morphology of BMSCs was changed under the SMG condition and thus had larger capability to differentiate to other cell types. This result further demonstrated that there was some interplay between the geometric cues of the cells and their functions (Kilian et al 2010). While previous report illustrated that SMG was helpful to expand stem cell populations in vitro (Yuge et al 2006), our work further demonstrated that SMG enabled cells to maintain pluripotency and therefore enhance multipotential differentiation capacity.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…We demonstrated that the morphology of BMSCs was changed under the SMG condition and thus had larger capability to differentiate to other cell types. This result further demonstrated that there was some interplay between the geometric cues of the cells and their functions (Kilian et al 2010). While previous report illustrated that SMG was helpful to expand stem cell populations in vitro (Yuge et al 2006), our work further demonstrated that SMG enabled cells to maintain pluripotency and therefore enhance multipotential differentiation capacity.…”
Section: Discussionsupporting
confidence: 66%
“…Geometric shape cues have shown to have great effect on the differentiation of human BMSCs (Kilian et al 2010). McBeath and his coworkers recently confirmed that cell shape and size had a large effect on the fate of MSCs (McBeath et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, 2D adhesive patterns of different sizes, shapes or aspect ratios have been used to demonstrate how stem cell differentiation is influenced by the shape of either individual cells or multicellular structures 10, 14, 22. The results presented here show that 3D substrate geometries of equal size and shape but of opposite curvature (convex vs concave) can also have a significant influence of osteogenic marker expression.…”
Section: Resultsmentioning
confidence: 78%
“…Numerous studies have shown that the mechanical properties of the cell's microenvironment, such as the substrate stiffness, have a fundamental effect on hMSC cell fate and function and impact tissue regeneration 6, 7, 8, 9. Recently, evidence is rising that the geometrical properties of the cell's environment also play an important role as regulators of cell behavior 10, 11, 12, 13, 14, 15, 16, 17, 18, 19. Using geometric features, such as pore geometry, as a cue to direct tissue regeneration is compelling since it may allow a biomaterial to steer cell function purely by its shape and hereby contribute to tissue regeneration.…”
Section: Introductionmentioning
confidence: 99%
“…These three different peptide designs demonstrate that alteration of the position of the β‐sheet‐forming amino acids and charge distribution of the sequence serves as a unique approach to control the morphology and tune the mechanical properties of the resultant hydrogel. Both substrate stiffness and substrate shape have been shown to influence cellular behavior 29, 30, 42. Therefore, with control over both of these parameters, the hydrogels have potential to act as tissue‐engineering scaffolds and matrices.…”
mentioning
confidence: 99%